RodZ and PgsA Play Intertwined Roles in Membrane Homeostasis of Bacillus subtilis and Resistance to Weak Organic Acid Stress - van Beilen, Johan; Blohmke, Christoph J.; Folkerts, Hendrik; de Boer, Richard; Zakrzewska, Anna; Kulik, Wim; Vaz, Fred M.; Brul, Stanley; Ter Beek, Alexander (Frontiers in Microbiology, 2016)
Weak organic acids like sorbic and acetic acid are widely used to prevent growth of spoilage organisms such as Bacilli. To identify genes involved in weak acid stress tolerance we screened a transposon mutant library of Bacillus subtilis for sorbic acid sensitivity. Mutants of the rodZ (ymfM) gene were found to be hypersensitive to the lipophilic weak organic acid. RodZ is involved in determining the cell’s rod-shape and believed to interact with the bacterial actin-like MreB cytoskeleton. Since rodZ lies upstream in the genome of the essential gene pgsA (phosphatidylglycerol phosphate synthase) we hypothesized that expression of the latter might also be affected in rodZ mutants and hence contribute to the phenotype observed. We show that both genes are co-transcribed and that both the rodZ::mini-Tn10 mutant and a conditional pgsA mutant, under conditions of minimal pgsA expression, were sensitive to sorbic and acetic acid. Both strains displayed a severely altered membrane composition. Compared to the wild-type strain, phosphatidylglycerol and cardiolipin levels were lowered and the average acyl chain length was elongated. Induction of rodZ expression from a plasmid in our transposon mutant led to no recovery of weak acid susceptibility comparable to wild-type levels. However, pgsA overexpression in the same mutant partly restored sorbic acid susceptibility and fully restored acetic acid sensitivity. A construct containing both rodZ and pgsA as on the genome led to some restored growth as well. We propose that RodZ and PgsA play intertwined roles in membrane homeostasis and resistance to weak organic acid stress.